Pengaruh Pola Tanam Terhadap Pertumbuhan Gulma dan Komponen Produksi Tanaman Padi Sawah (Oryza sativa L.) - Irwansyah irwansyah; Bhaidawi Bhaidawi; Muhammad Yusuf N (Agrium, 2017)
The principle of planting system “Jajar Legowo” is to increase the plant population by adjusting the spacing so that the crop will have a row of plants interspersed by empty rows where the spacing is on the row of rows half the spacing between rows. The purpose of this study to investigate the effect of different rice cropping patterns on weed growth. The research was conducted at Gampong Lhok Iboh, Baktiya district Barat North Aceh Regency started from March to June 2017. This research used non factorial Randomized Block Design which consists factor with 2 treatments: P1 (conventional cropping pattern) and P2 (jajar legowo). Observations included the amount of dominance (%), plant height (cm), number of tillers, panicle length, number of grains per panicle, and weight of 1000 grains per plot. The results revealed that cropping pattern had an effect on weed growth and production component of paddy. Planting system “jajar legowo” 2: 1 (25cm x 25 cm x 40 cm) was much better compared to conventional cropping pattern